Pak Ogah dan Realitas Marginalisasi: Kajian Sosial-Teologis Masyarakat Urban Banjarmasin - Angela, Maria Apriana; Maleh, Kinurung; Sudianto, Sudianto (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2025)
This paper aims to describe Pak Ogah as a social phenomenon within urban society. This descriptive qualitative research employs data collected through interviews, observations, and literature studies. The findings reveal that individuals who voluntarily manage traffic at road turns and intersections without traffic lights are commonly referred to as Pak Ogah. The Pak Ogah phenomenon can be understood as a rational choice made by the urban poor in their struggle for survival. It represents a marginalized community that is compelled to accept the label of “illegal workers” because their activities contradict traffic regulations. Establishing informal relations with the police, promoting Pak Ogah as a noble occupation for assisting road users, and maintaining good conduct are survival strategies that enable them to continue earning a livelihood amid the bustle of city life. Ultimately, this study recommends that both the government and the church undertake educational initiatives, social awareness campaigns, and economic empowerment programs for the Pak Ogah community.